NIR-II Fluorescence Imaging Using Indocyanine Green Provides Early Prediction of Skin Avulsion-Injury in a Porcine Model - Gao S; Yu Y; Wang Z; Wu Y; Qiu X; Jian C; Yu A (Dove Medical Press, 2022)
Siqi Gao,* Yifeng Yu,* Zheng Wang, Yifan Wu, Xingan Qiu, Chao Jian, Aixi Yu Department of Orthopedics Trauma and Microsurgery, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, 430071, People's Republic of China*These authors contributed equally to this workCorrespondence: Aixi Yu; Chao Jian, Department of Orthopedics Trauma and Microsurgery, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, 430071, People's Republic of China, Tel +86-27-6781-3120 ; +86-27-6781-3120, Email yuaixi@whu.edu.cn; chaojian@whu.edu.cnPurpose: Currently, skin avulsion-injury reconstruction is mainly based on subjective evaluation of traditional clinical signs. It frequently results in unnecessary tissue loss and incomplete debridement-related infection. This pilot study aimed to develop a novel near-infrared (NIR) II fluorescence imaging method to assess avulsed skin-perfusion status and thus predict its outcome early.Methods: Skin avulsion-injury models were established by avulsing 10× 4 cm pedicled flaps on porcine hindlimbs. A clinically available improved NIR-&Igr;/II multispectral imaging system was applied for NIR imaging using indocyanine green (ICG) fluorescence. Continuous NIR-wavelength filters and dynamic imaging were used to investigate optimal imaging conditions and time window. NIR-&Igr;/II imaging was synchronously conducted for quality comparison of the two methods. Visual inspection and histological studies were used for assessing the final outcome of avulsed skin.Results: NIR-II fluorescence imaging with a 1,100 nm filter obtained satisfactory performance and reached maximum fluorescence intensity at 1 minute after ICG injection. NIR-II imaging clearly visualized the microvascular network in vascularized avulsed skin and revealed "dark areas" in nonvascularized avulsed skin in a real-time fashion. NIR-II fluorescence imaging demonstrated higher resolution than NIR-I imaging, as indicated by ae higher signal-to-background ratio (2.11) and lower full width at half maximum (6.50614). The dark area of avulsed skin on imaging finally developed to necroses that were confirmed by histology.Conclusion: NIR-II real-time fluorescence imaging clearly maps the microvascular network and shows the perfusion status of avulsed skin at higher resolution than traditional NIR-I imaging, and thus precisely predicts the outcome of avulsed skin early.Keywords: ICG, near-infrared fluorescence imaging, skin avulsion-injury, swine model